ANALYSIS AIRCRAFT COMPONENTS INDUSTRY RECOVERY IN INDONESIA: INTEGRATION OF DELPHI - INTERPRETIVE STRUCTURAL MODELING (ISM) - Jupriyanto Jupriyanto; I Nengah Putra; A. K. Susilo (AL ULUM: JURNAL SAINS DAN TEKNOLOGI, 2026)
This study aims to analyze key factors for industrial recovery by identifying and modeling important factors for the recovery of the Indonesian aircraft component industry using a qualitative descriptive statistical method approach with eight experts. The Delphi method and Interpretive Structural Modeling (ISM) were used in this study to obtain expert consensus and map causal and hierarchical relationships between factors. The main findings reveal that key factors for industrial recovery fall into four groups: autonomous, interconnected, dependent, and driving. Furthermore, the findings reveal five hierarchical levels of relationships among recovery factors in the aircraft component industry. The order of practical application of industrial recovery factors ascends from level five to level one.